Stabilization of a copper peroxido complex with a new binucleating ligand - Wuertele, Christian; Heinemann, Frank Wilhelm; Schindler, Siegfried (Journal of Coordination Chemistry, 2010)
The ligand L(1) (N1,N3-di[2-di(2-pyridylmethyl)aminoethyl]N1,N3-dimethyl-1,3-propandiamine) bridges two tripodal units of the amine ligand Me(2)uns-penp (N1,N1-dimethyl-N2,N2-di(2-pyridylmethyl)-1,2-ethandiamine) with a propyl group. The ligand L(1), the dinuclear copper(I) complex [Cu(2)(L(1))](BPh(4))(2) and the dinuclear copper(II) complexes [Cu(2)Cl(2)(L(1))](ClO(4))(2), and Cu(2)Cl(2)(L(1))]Cl(2) have been synthesized and structurally characterized. The copper(I) complex reacts reversibly with dioxygen at low temperatures and forms a peroxido complex that is thermally more stable than the related peroxido complex formed from two mononuclear copper(I) complexes of the ligand Me(2)uns-penp.
Keywords: Copper; X-ray crystallography; Peroxido complexes; Low-temperature stopped-flow studies; Tripodal tetradentate ligand